The origin of early Israel--current debate
1 online resource (176 pages)
Keywords: "The origin of Israel, their settlement in the land of Canaan and transformation into an organized kingdom is one of the most stimulating and controversial chapters in the history of ancient Israel. In this volume, three of the researchers who have presented key models regarding this era--Finkelstein, Whitelam, and Kitchen--offer their latest thinking and are critiqued by a panel of other scholars, using biblical, historical, archaeological, anthropological and comparative Near Eastern data. An important introduction to the debate over this crucial question."--Provided by publisher.